Uncovering the Intellectual Structure of Research in Business Ethics: A Journey Through the History, the Classics, and the Pillars of Journal of Business Ethics - Calabretta, Giulia; Durisin, Boris; Ogliengo, Marco (2011)
After almost 30 years of publications, Journal of Business Ethics (JBE) has achieved the position of main marketplace for business ethics discussion and knowledge generation. Given the large amount of knowledge produced, an assessment of the state of the art could benefit both the constructive development of the discipline and the further growth of the journal itself. As the evolution of a discipline is set to be reflected in the evolution of its leading journal, we attempt to characterize changes in the intellectual structure of business ethics through a bibliometric analysis of articles published in JBE. Specifically, we conduct a knowledge-stock analysis to assess the evolution, major trends, and current state of the journal. Additionally, we use citation and co-citation analysis to provide an accurate description of the content and the advancement of research in business ethics. Through the results of our analysis, we are able to: (1) pinpoint the characteristics of the growing stock of knowledge published by JBE over the years; (2) identify the most influential works on business ethics research; and (3) detect the formation and evolution of schools of thought in business ethics.
Keywords: Literature Review; Bibliometrics; Ethical decision making; Corporate Social Responsibility; Business Ethics